The US-China trade war: the effects on the soybean industry - Hao, Xijian (Kansas State University, 2019)
The growing industry of soybean has been affected as never before due to the global economic slowdown, especially under the threat of the trade war between the U.S. and China that began in 2018. As the largest buyer of soybeans in the international market, China relies heavily on imports of foreign soybeans to meet the growing domestic production of meat and poultry. The U.S. is one of the world’s largest soybean exporters, and China used to buy 60% of U.S. soybean exports, but now the number was dropped to 20-25%. This article will analyze the ongoing trade war between China and the U.S., as China already increased tariffs on U.S. soybean export, how it would affect the soybean industry. The regression analysis of supply and demand model was used to explain which factors affect the soybean supply and demand of the two countries.
Keywords: Trade war; Soybean; Econometric models